Lamellibrachia anaximandri n. sp., a new vestimentiferan tubeworm (Annelida) from the Mediterranean, with notes on frenulate tubeworms from the same habitat - Southward, E. C.; Andersen, A. C.; Hourdez, S. (Zoosystema, 2011)
A new species of lamellibrachiid vestimentiferan, Lamellibrachia anaximandri n. sp., has been found in the Eastern Mediterranean, close to cold seeps of fluid carrying dissolved methane and sources of sulfide in superficial sediments. It occurs at about 1100 to 2100 m depth, on some of the mud volcanoes on the Anaximander Mountains, south of Turkey, on the Mediterranean Ridge, south of Crete, and on the Nile deep-sea fan. In addition, it has been obtained from rotting paper inside a sunken ship, torpedoed in 1915 and lying at 2800 m depth, southeast of Crete. Some frenulate pogonophores also occur on the mud volcanoes (including a species of Siboglinum resembling S. carpinei and tubes of other unidentified genera). The new Lamellibrachia is the first vestimentiferan species to be described from the Mediterranean. It differs from L. laymesi taken from the Gulf of Mexico population in the very weak development of collars on its tube and in having a smaller number of pairs of branchial lamellae in the branchial plume. Sequencing of the COI and the mt16S genes confirms a difference at the species level between the new species and L. luymesi, and a difference between these two species and four described species of Lamellibrachia from the Pacific Ocean. The largest individuals of L. anaximandri n. sp. may be many years old, but there are numerous young individuals at some sites, showing that favourable conditions are available for settlement and early growth. The development of the branchial plume in a series of young stages reveals that the sheath lamellae, which are characteristic of the genus Lamellibrachia, begin to form only after the establishment of several pairs of branchial lamellae. Examination of the adult trophosome by transmission electron microscopy shows Gram-negative bacteria without internal stacked membranes, indicating that the symbionts are most probably sulfide oxidizing.
World Polychaeta Database